Preparation of Silver Doped Poly(L-Cysteine Acid) Modified Electrode and its Determination for Uric Acid - Ma, Wei; Yao, Xue; Sun, Dengming (Asian Journal of Chemistry, 2011)
The silver doped poly(L-cysteine acid) modified electrode was prepared by cyclic voltammetric method. The voltammetric behaviour and cyclic voltammetric method determination of uric acid were studied at the modified electrode. In pH 3.0 phosphate buffer solution, the linear ranges for the determination of uric acid were 5.00 × 10-7-1.00 × 10-4 M and 1.00 × 10-4-5.00 × 10-4 M with the detection limit of 1.0 × 10-7 M. The method was applied to the determination of uric acid in urine with satisfactory results.